Maternal tobacco use: A third-trimester risk factor for small-for-gestational-age pregnancy outcome - Lamm, Steven H. (Prev Med Rep, 2020)
BACKGROUND: Small for gestational age (SGA) is a well-known consequence of maternal smoking. Here, we newly examine the magnitude of SGA risk by week of gestational age. METHODS: Singleton live births (N = 3,032,928) with recorded birth weight, gestational age (22–44 weeks), and maternal tobacco use (Y/N) were categorized as to SGA (Y/N), based on 10th percentile gender-specific weights-for-age. RESULTS: SGA prevalence among tobacco users (19.5%) and non-users (9.1%) yielded a significant SGA prevalence rate ratio of 2.15 (2.13–2.16) and a significant adjusted odds ratio of 2.36 (2.34–2.38). The tobacco non-users’ rate was steadily near 9% across the week 22–44 gestational age range. The tobacco users’ rate was steady until week 33 when it rose monotonically through week 37 to about 20% at week 38 and remained high. This pattern for SGA by gestational week was similar for prevalence rates and adjusted ORs. Tobacco use only through week 33 was not seen to be an SGA risk factor. The magnitude of tobacco use as an SGA risk factor for late third trimester births increased during the period of preterm birth and became fully evident with a two-fold risk for full term infants. CONCLUSION: We newly report the temporal pattern of tobacco-related SGA by week of gestational age. Tobacco-related SGA was only seen for late third trimester births – increasing during weeks 33–37 with a doubling during weeks 38–44. This pattern, informative for issues of mechanism, highlights the potential benefit of extending tobacco cessation programs through the third trimester of pregnancy.